Bovine digital dermatitis: Current concepts from laboratory to farm. (May 2016) - Evans, N.J.; Murray, R.D.; Carter, S.D.
Highlights: Bovine digital dermatitis (DD), DD treponemes, DD risk factors and DD control strategies are reviewed. DD lesions, hoof trimming tools and bovine GI tract are DD infection reservoirs. Improved hygiene and foot trimming practice could help prevent DD transmission. Current antibiotic treatments are not the most effective against DD treponemes. New antibiotics, additional transmission prevention and/or effective vaccines are needed. Abstract: Bovine digital dermatitis (DD) is a severe infectious disease causing lameness in dairy cattle worldwide and is an important ruminant welfare problem that has considerable economic issues. Bovine DD is endemic in many regions worldwide and it is important to understand this major disease so that effective control strategies can be identified. There is substantial evidence that specific treponeme phylotypes play an important causative role in bovine DD. This review considers current research, including DD Treponema spp. investigations, associated DD pathobiology, and current and potential treatment and control options. Epidemiological data, alongside new microbiological data, help delineate important transmission routes and reservoirs of infection that allow effective interventions to be identified. Better on-farm housing hygiene, pasture access, routine footbathing and claw trimming with disinfected equipment need to be implemented to significantly reduce the incidence of DD. There is a paucity of peer reviewed research into both commonly used and novel treatments. In vitro antimicrobial susceptibility studies of DD treponemes and effective treatment of human treponematoses clearly indicate that antibiotics frequently selected for DD treatments are not the most efficacious. Whilst there are understandable concerns over milk withdrawal times in dairy cattle, more needs to be done to identify, license and implement more appropriate antibiotic treatments, since continued overuse of less efficacious antibiotics, applied incorrectly, will lead to increased disease recurrence and transmission. More research is needed into methods of preventing DD that circumvent the use of antibiotics, including vaccination and transmission blocking studies, to reduce or hopefully eradicate DD in the future.